Analisis Sistem Pembiayaan Akad Rahn di BMT Mandiri Sejahtera Jawa Timur Cabang Benjeng Kota Gresik - Ahmad, Walid In'am; Rahman, Taufiqur (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to describe the financing system of the rahn contract in the KSPPS BMT Mandiri Sejahtera East Java Benjeng Gresik Branch. This type of research is qualitative descriptive research, that is, research that describes the object of research as it is. This study is not intended to test a particular hypothesis and therefore does not require control over a treatment. Research data were collected through observation, interviews, documentation. The results of the study are: 1) Terms and conditions of financing using a rahn contract at BMT Mandiri Sejahtera East Java using guarantees in the form of goods such as BPKB / STNK motor vehicles or BMT savings cards and this serves to hold the borrower's assets as collateral for the loan money he receives; 2) The rahn contract financing system at BMT Mandiri Sejahtera East Java is for active members of BMT who have principal savings and even those who are not members of BMT; 3) The benefits of the rahn contract for members are to help members who have difficulty in paying debt installments and at the same time as a source of easier and safer loans.